Perianal Plaques of Cytomegalovirus in a Patient with Central Nervous System Lymphoma - Scott K. Heysell; Brian Wispelwey (Case Reports in Infectious Diseases)
Cutaneous manifestations of cytomegalovirus (CMV) in patients without human immunodeficiency virus remain rare. Perianal CMV may be observed due to periodic fecal shedding but may be confused for other pathogens, and definitive diagnosis requires histopathologic examination. An instructive case is described, and the literature reviewed.